2022
DOI: 10.3389/fpubh.2022.952378
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of colonoscopy and fecal immunochemical testing for colorectal cancer screening in China

Abstract: ObjectiveThis study aimed to evaluate the cost-effectiveness of the colorectal cancer screening in China, and that when the screening was implemented in a specific region.MethodsA 13-state Markov model was established to compare four screening protocols, including annual fecal immunochemical testing (FIT1), biennial fecal immunochemical testing (FIT2), electronic colonoscopy every 10 years (e-CSPY10), and electronic colonoscopy every 5 years (e-CSPY5), with no screening from the perspective of Chinese healthca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…8 Ren et al developed a periodic FIT-based and Cost-benefit of one-time colonoscopy colonoscopy-based strategy, compared the cost-effectiveness of the Chinese insurance system, and found that the FIT-based strategy was more cost-effective for all ages. 19 In a meta-analysis of CEA comparing single colonoscopy with multiple FITs, the FIT-based strategy was more cost-effective. 20 This model is a screening strategy based on multiple colonoscopies or FITs, which are difficult to implement owing to the limited medical resources available.…”
Section: Discussionmentioning
confidence: 99%
“…8 Ren et al developed a periodic FIT-based and Cost-benefit of one-time colonoscopy colonoscopy-based strategy, compared the cost-effectiveness of the Chinese insurance system, and found that the FIT-based strategy was more cost-effective for all ages. 19 In a meta-analysis of CEA comparing single colonoscopy with multiple FITs, the FIT-based strategy was more cost-effective. 20 This model is a screening strategy based on multiple colonoscopies or FITs, which are difficult to implement owing to the limited medical resources available.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional methods for the diagnosis of CRC have their own obvious shortcomings, such as poor patient compliance rate in colonoscopy and low diagnostic accuracy in FOBT, FIT and other serum tumor biomarkers [3][4][5][6][7]. Consequently, developing a noninvasive and reliable method for detecting CRC is critical.…”
Section: Discussionmentioning
confidence: 99%
“…At present, some conventional methods for CRC detection, such as colonoscopy (the gold standard for CRC diagnosis), fecal occult blood test (FOBT) or fecal immunochemical test (FIT) (the most widely used screening biomarkers for CRC diagnosis) and carcinoembryonic antigen (CEA) or carbohydrate antigen-199 (CA199) all contain several limitations, such as uncomfortable experience, high costs, susceptible to interference, low sensitivity and low speci city [3][4][5][6][7]. Thus, identifying a patient-friendly approach with high diagnostic accuracy is crucial to improve the clinical outcome of CRC patients.…”
Section: Introductionmentioning
confidence: 99%
“…The annual transition probabilities from one status to another were used as the input. For the annual transition probability of CRC, we referred to the value reported by Ren et al 11 and Li et al 12 (from non-advanced adenoma to advanced adenoma, 2%; from advanced adenoma to local cancer: 4.4%; from local to regional cancer, 30% [25–35%]; and from regional to distant cancer, 50% [45–55%]).…”
Section: Methodsmentioning
confidence: 99%